10 years of Outcome Mapping - Smith, R; Mauremootoo, John; Ambrose, K.; Hearn, Simon (2012)
This webinar from the Outcome Mapping Learning Community (OMLC) presen ts the key findings from research conducted into the extent of Outcome Mapping use and the support required for its implementation.